ASSOCIATION OF STRESS LEVEL WITH GENDER, SEMESTER OF STUDY AND CLINICAL PRACTICE IN UNDERGRADUATE PHYSICAL THERAPY STUDENTS: A CROSS SECTIONAL SURVEY - Ashraf, Hafiza Sana; Sohail, Maria; Tanveer, Fahad; Farooq, Haris; Masood, Haleema (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find association of stress level with gender, semester of study and clinical practice in undergraduate physical therapy students.Study Design: Cross sectional observational survey.Place and Duration of Study: Superior University, University of Management and Technology, University of Lahore, Lahore Medical and Dental College and Imperial University, from Apr to Jul 2019.Methodology: Study was conducted on 358 students of physical therapy. Non-probability purposive sampling technique was used for data collection. Standard student Stress Inventory scale was used for the measurement of stress among students.Results: Mean age of all the students in this study was 21.26 ± 1.997 with minimum of 18 years and with maximum of 25 years. There were 254 (70.9%) female students and 104 (29.1%) male students who participated in the study. Results showed 14.15% “Mild Stress”, 58.44% “Moderate Stress” and 27.4% “Severe Stress” in “Pre-Clinical Stage (1st - 4th semester)”. Chi-square test described a p-value of